PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 21 PEKANBARU - Sarmesta Junika Sarmesta Junika; Mahmud Alpusari Mahmud Alpusari; Zariul Antosa Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to improve students learning outcomes third grade of SDN 21 Pekanbaru use the Model-Based on Learning Problem. The subject of this study is the third grade students of SDN 21 Pekanbaru the number of students are 38 students, consist of 21 girls and 17 boys. This study was conducted in three cycles, each cycle consisting of two materials and one-time daily tests for each cycle. Instrument collecting data in this study is a teacher and student activity sheets and student learning outcomes. Before action student ability level is categorized to low level that mean is 64.21. While the value of a minimum completeness criteria (KKM) IPA is 70. Among 38 students only 14 students who reach KKM with 36.84% classical completeness. The first Daily test to 68.82 increased to 7.12% points., the second Daily test increased to 69.60 by 8.39% points and the third Daily test increased to 84.44 by 26.83% points increase , The average score of teacher activity was 70% at the first meeting the first cycle increased to 75% in the second meeting. At the first meeting of the second cycle an average was 85% of teacher activity score increased to 90% in the second meeting. While the third cycle an average score was 95% with the teachers activity is very good category. Learning activities of students in learning process has increased at each meeting from an average was 65% in the first meeting of the first cycle increased to 70% in the second meeting. At the first meeting of the second cycle increased to 75% and 85% in the second meeting. While the third cycle an average was 90% increased to 95%. From the explanation above proves that the implementation of Learning Based on Problem Model to improve learning outcomes IPA third grade students of SDN 21 Pekanbaru.Keywords: Problem Based Learning Model, IPA Learning Outcomes